Bipolar disorder in children and adolescents: an update on diagnosis. (December 2014) - Rizvi, Sabeen H; Ong, Mian-Li; Youngstrom, Eric A
Converging evidence from both community and clinical settings shows that pediatric bipolar disorder is a valid diagnosis and a debilitating condition. While the field has evolved considerably, there remain gaps in diagnosis, assessment, research and practice. This article critically appraises advances in understanding of the phenomenology of pediatric bipolar disorder; changes in diagnostic criteria from the Diagnostic and Statistical Manual (DSM)-IV to DSM-5 and corresponding controversies; the epidemiology of pediatric bipolar disorder; current assessment and diagnostic practices; and cultural factors influencing treatment seeking and diagnosis. We recommend using an evidence-based framework for bridging the gap between research and clinical practice.